2017
DOI: 10.1051/bsgf/2017206
|View full text |Cite
|
Sign up to set email alerts
|

Vertical strain partitioning in hot Variscan crust: Syn-convergence escape of the Pyrenees in the Iberian-Armorican syntax

Abstract: -A new structural map of the Paleozoic crust of the Pyrenees based on an extensive compilation and new kinematic data allows for the evaluation of the mechanical coupling between the upper and lower crust of the abnormally hot foreland of the Variscan orogen of SW Europe. We document partitioning between coeval lower crustal lateral flow and upper crustal thickening between 310 and 290 Ma under an overall dextral transpressive regime. Partitioning also involved syn-convergence transtensional gneiss domes empla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(119 citation statements)
references
References 123 publications
5
110
0
Order By: Relevance
“…Gutiérrez‐Alonso et al () suggested that buckling involves asthenosphere‐lithosphere interactions producing delamination or thermal erosion. These processes imply the soft character of the surrounding lithosphere that is able to escape from the closing structure by lateral flow along the branches of the arc, for example, along the North Pyrenean shear zone or the SASZ (Augier et al, ; Cochelin et al, ; Gapais et al, ; Llana‐Fúnez & Marco, ). From that point of view, the SASZ could have acted as a transfer zone between the cold Central Armorican domain and the hot South Armorican domain (Gapais et al, ), in a manner similar to other arcuate belts like the Aegean, the Apennine‐Calabria, and the Rif‐Gibraltar‐Betics regions (Brun & Faccenna, ; Faccenna et al, ; Palano et al, ; Rutter & Valetti, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gutiérrez‐Alonso et al () suggested that buckling involves asthenosphere‐lithosphere interactions producing delamination or thermal erosion. These processes imply the soft character of the surrounding lithosphere that is able to escape from the closing structure by lateral flow along the branches of the arc, for example, along the North Pyrenean shear zone or the SASZ (Augier et al, ; Cochelin et al, ; Gapais et al, ; Llana‐Fúnez & Marco, ). From that point of view, the SASZ could have acted as a transfer zone between the cold Central Armorican domain and the hot South Armorican domain (Gapais et al, ), in a manner similar to other arcuate belts like the Aegean, the Apennine‐Calabria, and the Rif‐Gibraltar‐Betics regions (Brun & Faccenna, ; Faccenna et al, ; Palano et al, ; Rutter & Valetti, ).…”
Section: Discussionmentioning
confidence: 99%
“…The West European Variscan belt exposes many large strike‐slip shear zones, revealing wrenching that largely contributed to orogenic construction (e.g., Arthaud & Matte, ; Gapais & Le Corre, ). These shear zones are interpreted as the result of (1) the accommodation of the lateral component of oblique convergence between Gondwana and Laurasia plates (Braid et al, ; Martínez Catalán, ; Pastor‐Galán et al, ; Shelley & Bossière, ), (2) the accommodation of indentation of an irregular pre‐Variscan Gondwanan margin (e.g., Braid et al, ; Brun & Burg, ; Casas & Murphy, ; Dias & Ribeiro, ; Matte & Ribeiro, ; Matte, ; Kroner & Romer, ; Llana‐Fúnez & Marco, ; Murphy et al, ; Perroud & Bonhommet, ; Quesada, ; Ribeiro et al, , ), and/or (3) the accommodation of oroclinal buckling leading to the Cantabrian orocline/Ibero‐Armorican Arc (Casas & Murphy, ; Cochelin et al, ; Edel et al, ; Gutiérrez‐Alonso et al, ; Llana‐Fúnez & Marco, ; Martínez Catalán, ; Murphy et al, ; Pastor‐Galán et al, ; Ribeiro et al, ; Shaw et al, ; Figure a). Many of these strike‐slip shear zones bound gneiss domes and were active during exhumation of their cores with different tectonic scenarios proposed: transfer zones (Augier et al, ; Gapais et al, ), pull‐apart bounding structures (Echtler & Malavieille, ; Roger et al, ), or transpressional zone boundaries (Cochelin et al, ; Denèle et al, , ; Rabin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gibson, 1991;Vissers, 1992;Wickham & Oxburgh, 1986); 3) regional transpression (e.g. Carreras & Capella, 1994;Cochelin et al, 2017;Denèle, Olivier, Gleizes, & Barbey, 2009;Druguet, 2001;Gleizes, Leblanc, & Bouchez, 1998;Mezger, 2009). The latter have progressively evolved from models invoking pure transpression (e.g.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…Carreras & Capella, 1994) to those admitting a significant contribution of localised extension (e.g. Cochelin et al, 2017;Mezger & Passchier, 2003).…”
Section: Tectonic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation